Unusual Nanofractal Microparticles for Rapid Protein Capture and Release. Issue 36 (28th July 2021) - Song, Yongyang; Dong, Xuefang; Shang, Danyi; Zhang, Xiaofei; Li, Xiuling; Liang, Xinmiao; Wang, Shutao
Abstract: Ion exchange porous microparticles are widely used for protein separation, but their totally porous structure often leads to slow diffusion rate and long separation time. Here unusual nanofractal microparticles synthesized by a strategy of electrostatic interaction regulated emulsion interfacial polymerization are demonstrated that exhibit excellent capability of rapid protein capture, release, and separation. The growth of nanostructures at nanofractal microparticle surface can be controlled by changing electrostatic repulsion between ion groups from weak to strong. The nanofractal microparticles provide a 3D contact model between ion groups and proteins, enable fast protein diffusion rate at initial capture and release stage, and realize rapid and efficient separation of similarly sized proteins as a proof of concept, superior to porous microparticles. This strategy offers an effective and general way for the synthesis of microparticles towards rapid and efficient separation in various fields of biomedicine, environment, and food. Abstract : Nanofractal microparticles, synthesized by electrostatic interaction regulated emulsion interfacial polymerization, can separate similarly sized proteins rapidly and efficiently. The growth of nanostructures at nanofractal microparticle surface can be controlled by changing electrostatic repulsion from weak to strong. They provide a 3D contact model between ion groups and proteins, enable fast protein capture, release, and separation, superior to porous microparticles.